Designing A Fintech Crowdfunding Business Model to Support the Sustainability of Small-Scale Coffee Farmers in Dairi Regency - Simangunsong, Denny Indra Simson; Rahadian , Dadan (International Journal Labs, 2025)
Small-scale coffee farmers in Dairi Regency, Indonesia, face significant challenges in accessing capital, primarily due to low financial literacy, coffee price volatility, and limited assets for collateral. These issues hinder farmers from adequately maintaining their coffee plants, resulting in constrained production and declining crop productivity. Financial technology (fintech) crowdfundingcrowdfunding offers a potential solution to improve access to financing and enhance the sustainability of farming enterprises. This study aims to design a fintech crowdfundingfintech crowdfundingcrowdfunding business model that addresses the needs of small-scale coffee farmers in Dairi Regency, facilitating easier access to capital, enhancing supply chain transparency, and promoting the sustainability of their businesses. The study employs a qualitative approach, incorporating in-depth interviews with coffee farmers, lending service providers, and investors, alongside secondary data analysis. The Business Model Canvas (BMC) is applied to map customer segments and revenue streams, while the Value Design Model (VDM) is utilized to create value among stakeholders. This research is expected to produce an effective crowdfundingcrowdfunding business model tailored to support coffee farmers while inspiring investors to develop fintech crowdfundingfintech crowdfundingcrowdfunding solutions that align with the unique characteristics of small-scale coffee farmers in Indonesia.